Síntese de escopo de pesquisas que integram BIM e GIS aplicadas a infraestrutura urbana - Jesus, Guilherme Carlos de (2023)
The term GIS (Geographic Information System) comes from the English GIS (Geographic Information System). Urban infrastructure processes use digital mechanisms and platforms that collect and map and distribute information at different urban scales. Building Information Modelling (BIM) contemplates the objective of managing the life cycle of a volume to be implemented at a local scale, while GIS works by capturing and mapping characteristics of existing urban conditions for analysis, management and prevention. The integration relationship between the BIM and GIS platforms is a promising topic for urban management processes, arising from the concept of CIM (City Information Modelling), which consists of the modelling of management flows in processes for cities or territories through the use of integration between BIM and GIS. The promising integration of BIM and GIS in urban processes on computational practices and tools help processes for Smart Cities, but it needs a dynamic between GIS and BIM platforms to reduce information loss during the process of exchange and collection of data (Import and Export). Integration has challenges in terms of reading and converting data between platforms, as the platforms were originally developed for different purposes. The research will carry out the systematic literature review (RSL) methodology, will collect the results acquired from the current state of the art on the integration strategies of BIM and GIS in various infrastructure sectors and will seek to identify their limitations, potentials, impacts and what they are the sectors with the highest adhesion to the integration of BIM and GIS, seeking to understand the frontier of knowledge through a bibliometric analysis on which are the main researches in the area, which countries that had the highest number of articles published on the integration of BIM and GIS for processes urban management and which articles were more relevant among international databases.